Simple and efficient CRISPR/Cas9-mediated targeted mutagenesis in Xenopus tropicalis - Nakayama, Takuya (2013)
We have assessed the efficacy of the recently developed CRISPR/Cas (clustered regularly interspaced short palindromic repeats/CRISPR-associated) system for genome modification in the amphibian Xenopus tropicalis. As a model experiment, targeted mutations of the tyrosinase gene were verified, showing the expected albinism phenotype in injected embryos. We further tested this technology by interrupting the six3 gene, which is required for proper eye and brain formation. Expected eye and brain phenotypes were observed when inducing mutations in the six3 coding regions, as well as when deleting the gene promoter by dual targeting. We describe here a standardized protocol for genome editing using this system. This simple and fast method to edit the genome provides a powerful new reverse genetics tool for Xenopus researchers.